The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-40277/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the effect of Chamomile and Mefenamic Acid on primary dysmenorrhea, associated symptoms and menstrual bleeding – A randomized clinical trial study

Abstract: Background Dysmenorrhea is one of the most common pelvic pains in women, impairing their quality of life.This study investigated the effects of chamomile sachet and mefenamic acid on primary dysmenorrhea, associated symptoms and bleeding. Methods In this randomized clinical trial, 200 female students with primary dysmenorrhea from Arak universities were randomly assigned to two groups. The group (A) received mefenamic acid (250 mg) and group (B) received chamomile (5000 mg) plus one teaspoonful of honey )as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Various studies have reported the dramatic alleviation of dysmenorrhea associated with PMS, either alone or in combination with other complementary therapies [23][24] . However, the effect of mefenamic acid alone on overall symptoms of PMS is not appraised appropriately especially among the people of Pakistan.…”
Section: Yes Nomentioning
confidence: 99%
“…Various studies have reported the dramatic alleviation of dysmenorrhea associated with PMS, either alone or in combination with other complementary therapies [23][24] . However, the effect of mefenamic acid alone on overall symptoms of PMS is not appraised appropriately especially among the people of Pakistan.…”
Section: Yes Nomentioning
confidence: 99%